Inovasi Mobilitas Lansia dengan Alat Bantu Jalan Terintegrasi Cakar Derek - Abdillah, Sultansyah Reza; Nugraha, Fakhri Ihsan; Ong, Janice; Warsono, Kenneth Alden; Shobri, Muhammad; Endrasari, Fitri; Nurprasetio, Ignatius Pulung; Djamari, Djati Wibowo (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
Elderly-supporting technology is a continuously evolving field as new needs emerge and novel solutions are developed. This work addresses the challenge elderly individuals face in picking up objects from the floor, a task often painful or difficult for those with back pain. Currently, no such assistive system is available on the market. This study aimed to develop a crane claw-integrated walking stick that enables object retrieval without bending, enhancing mobility and reducing fall risks. By integrating the claw with the walking stick, the design eliminates the need for an additional tool. Three design concepts, using repurposed 3D printer parts, were evaluated for performance, simplicity, and cost, resulting in the selection of a cable winch mechanism. Stress and fatigue analyses using SolidWorks ensured safety; the claw assembly exhibited a maximum stress of 7.238×10⁶ Pa, a safety factor of 4.8, and a fatigue life of 691,507 cycles. The product was fabricated from PLA with 50% infill and a tri-hexagonal pattern. A mechatronics system—comprising an Arduino UNO, DC motor, H-Bridge L298N module, and sensors—enabled precise control of the claw mechanism. The final device promotes independence and mobility for elderly users, offering a practical, ergonomic, and user-friendly solution.